The Effect of Parasocial Intervention on Purchase Intention with Consumer Online Purchase Behavior as an Intervention Variable in Fashion Products - Dede Suleman; Sofyan Marwansyah; Raden Ati Haryati; Devy Sofyanty; Dede Mustomi; Wiwin Wianti; Lukman Hakim (ProBisnis : Jurnal Manajemen, 2023)
This study aims to explore the relationship between parasocial interaction and purchase intention (Interest in Shopping) and how consumer online purchase behavior acts as an intermediary variable. The quantitative method used in this research is the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. Hypotheses are tested via statistical t tests. Data was collected through a questionnaire distributed to 211 respondents who were followers of Zara's social media accounts and had never purchased products from this brand. The research was conducted for 4 months, from February to May 2022. The results showed that parasocial interactions had a 54% influence on consumer online purchasing behavior, 39% on purchasing interest, and consumer online purchasing behavior had a 42% influence on purchasing interest. Apart from that, consumer online purchasing behavior also acts as an intermediary variable with an influence of 22%. This research provides insight into how parasocial interactions influence purchase intention and through what mechanisms consumers' online purchasing behavior plays a role in this relationship